1992
DOI: 10.1523/jneurosci.12-04-01416.1992
|View full text |Cite
|
Sign up to set email alerts
|

Periodic-pattern-selective cells in monkey visual cortex

Abstract: To study the visual processing of periodic and aperiodic patterns, we have analyzed neuronal responses in areas V1 and V2 of the visual cortex of alert monkeys during behaviorally induced fixation of gaze. Receptive field eccentricities ranged between 0.5 degrees and 4 degrees. We found cells that responded vigorously to gratings, but weakly or not all to bars and edges. In some cells the aperiodic stimuli even reduced the activity below the spontaneous level. The distribution of a bar-grating response index i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…These cells belonged to a larger group of cells that they called`texture cells'. The majority of these texture cells responded optimally to gratings, and the description of the cells fully complies with the description of the grating cells given by Von der Heydt et al (1992).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…These cells belonged to a larger group of cells that they called`texture cells'. The majority of these texture cells responded optimally to gratings, and the description of the cells fully complies with the description of the grating cells given by Von der Heydt et al (1992).…”
Section: Introductionsupporting
confidence: 68%
“…Von der Heydt et al (1991Heydt et al ( , 1992 reported on the properties of a speci®c type of orientation selective neuron in areas V1 and V2 of the visual cortex of monkeys that they called the grating cell. Similarly to other orientation selective neurons, such as simple, complex and hyper-complex cells, grating cells respond vigorously to a grating of bars of appropriate orientation, position and periodicity.…”
Section: Introductionmentioning
confidence: 99%
“…1999) the majority of orientationselective cells in V1 exhibit surround inhibition that leads to suppression of responses of texture. However, there are also neurons in V1 and V2, called grating cells, that show selective responses to oriented texture (von der Heydt et al 1991(von der Heydt et al , 1992du Buf 2007,Kruizinga andPetkov 1999). Furthermore, there are cells in MT, called wide-field neurons, that prefer large moving texture fields and exhibit no surround inhibition (Allman et al 1985;Born and Tootell 1992;Raiguel et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Only in the extreme case of complete suppression will the operator respond exclusively to single bars and not respond to gratings of any periodicity. Such neurons have occasionally been encountered in neurophysiological studies (Schiller et al 1976;von der Heydt et al 1992). At the opposite end of the function continuum of orientation-selective cells, one can find the grating cells (von der Heydt et al 1992), which respond optimally to gratings and, in the extreme case of ''gratingness,'' do not respond to single bars.…”
Section: Models Of Non-crf Inhibitionmentioning
confidence: 99%
“…2c was related to the function of a specific type of orientation-selective cell in the primary visual cortex for which the response to an optimal stimulus over the cell's classical (excitatory) receptive field (CRF) is influenced by other stimuli outside that area (Petkov and Kruizinga 1997). In contrast to other orientation-selective neurons, such as simple (Hubel and Wiesel 1968), complex (Hubel and Wiesel 1968), and grating (von der Heydt et al 1992) cells, the concerned type of neuron responds strongly to single bars (of appropriate size and orientation) over its CRF and shows reduced response when a grating is added to the surround. The behavior of such a cell was systematically studied by Blakemore and Tobin (1972).…”
Section: Introductionmentioning
confidence: 99%